2020
DOI: 10.1186/s12879-020-05030-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of Clostridium difficile in children with acute gastroenteritis from Zhejiang

Abstract: Background: Clostridium difficile infection (CDI) has an increasing pediatric prevalence worldwide. However, molecular characteristics of C. difficile in Chinese children with acute gastroenteritis have not been reported. Methods: A five-year cross-sectional study was conducted in a tertiary children's hospital in Zhejiang. Consecutive stool specimens from outpatient children with acute gastroenteritis were cultured for C. difficile, and isolates then were analyzed for toxin genes, multi-locus sequence type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recent work has found that patients critically ill with COVID-19 had secondary P. aeruginosa and Enterobacterales infections [19]. Further, patients with norovirus, adenovirus, astrovirus, and sapovirus have increased severity of C. difficile symptoms [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has found that patients critically ill with COVID-19 had secondary P. aeruginosa and Enterobacterales infections [19]. Further, patients with norovirus, adenovirus, astrovirus, and sapovirus have increased severity of C. difficile symptoms [20,21].…”
Section: Introductionmentioning
confidence: 99%